Research questions to facilitate the future development of European long-term ecosystem research infrastructures: A horizon scanning exercise - Musche, Martin; Adamescu, Mihai; Angelstam, Per; Bacher, Sven; Bäck, Jaana; Buss, Heather L; Duffy, Christopher; Flaim, Giovanna; Gaillardet, Jerome; Giannakis, George V; Haase, Peter; Halada, Luboš; et al. (Journal of environmental management, 2019)
Distributed environmental research infrastructures are important to support assessments of the effects of global change on landscapes, ecosystems and society. These infrastructures need to provide continuity to address long-term change, yet be flexible enough to respond to rapid societal and technological developments that modify research priorities. We used a horizon scanning exercise to identify and prioritize emerging research questions for the future development of ecosystem and socio-ecological research infrastructures in Europe. Twenty research questions covered topics related to (i) ecosystem structures and processes, (ii) the impacts of anthropogenic drivers on ecosystems, (iii) ecosystem services and socio-ecological systems and (iv), methods and research infrastructures. Several key priorities for the development of research infrastructures emerged. Addressing complex environmental issues requires the adoption of a whole-system approach, achieved through integration of biotic, abiotic and socio-economic measurements. Interoperability among different research infrastructures needs to be improved by developing standard measurements, harmonizing methods, and establishing capacities and tools for data integration, processing, storage and analysis. Future research infrastructures should support a range of methodological approaches including observation, experiments and modelling. They should also have flexibility to respond to new requirements, for example by adjusting the spatio-temporal design of measurements. When new methods are introduced, compatibility with important long-term data series must be ensured. Finally, indicators, tools, and transdisciplinary approaches to identify, quantify and value ecosystem services across spatial scales and domains need to be advanced.
Keywords: Priorities; Interoperability; ekologie; Research infrastructure; Europe; Whole system approach; Evropa; Research strategies; Ecology; ekosystém; Ecosystem